GC-MS determination of bioactive components of Erythropalum scandens Bl., Bijdr. - Sutha .S, Kalpana Devi .V, Mohan .V.R (Journal of Applied Pharmaceutical Science)
Erythropalum scandens Bl., Bijdr (Erythropalaceae) known to the Kanikkar as “Vaathavallikodi” is an important medicinal plant. The Kanikkar tribe, inhabitants of KMTR, Western Ghats, Tamil Nadu use this plant to relief from rheumatic pain. The present investigation deals with GC-MS analysis of ethanol extract of the above said plant. Forty one compounds were identified.
Keywords: GC-MS analysis, Erythropalum scandens, phytol.